„No” to Animals in Circuses - Kukiełko-Rogozińska, Kalina (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
The purpose of the paper is to present actions of the social campaign ‘Circus Without Animals’. More than twenty pro-animal associations from Poland (among others, Basta!, Viva!, and Empatia) established a coalition primarily focused on implementation of a legal ban on the use of animals in circuses in our country. Such solutions have already been introduced in several countries around the world as a result of the impact of civic initiatives. In Poland we still have no comprehensive solutions, however there are a lot of local initiatives in particular cities (for example, the Board of Education in Łódź forbade distribution of tickets to circuses in schools). The coalition, using the slogan ‘We trumpet against circuses’, is involved in educational activities (addressed mainly to children and youth, making up the majority of the circus audience), informing people about feelings and intelligence, but also about suffering of animals used for human entertainment.